Producer milk groups in Ethiopia's highlands: A framework for assessing impacts and a review of group performance - Nicholson, C.; Gebru, G.; Ehui, Simeon K.; Shapiro, Barry I.; Delgado, Christopher L. (MOA, 2000)
This paper discusses the potential impacts of the formation of milk groups on farm households that participate by selling milk, and develops a conceptual framework for assessing those impacts. It then explores the financial and technical performance of four milk groups formed prior to 1997, and the characteristics of the persons and businesses purchasing from them. Topics of discussion include increased milk production; increased income from dairy production and marketing changes in labour for processing and marketing; assessment of group financial and technical performance, and characteristics of group sales.